Correlation of Consistency and Compressibility Properties of Soils in Sulaimani City - Rashed, Kamal Ahmad; Salih, Nihad Bahaaldeen; Abdalla, Tavga Aram (Sulaimani Journal for Engineering Sciences, 2017)
Compressibility properties of soils are one of the most important properties in geotechnical engineering because of the needs for a safe and economic design for structures foundations. Compressibility parameters are used in the settlement calculations. Direct determination of both compression index (C c ) and recompression index (C r ) are costly, cumbersome and consuming time. These indices require undisturbed soil samples depending on a lot of experiences in the field works. Due to those factors, useful correlations were developed previously to predict compressibility properties. In the current study, the correlations conducted by using consistency properties, which are easy measurable variables. In this study, single (nonlinear equation) and multiple empirical equations were proposed to predict compressibility indices (C c and C r ) as a function of index properties (LL, PL, PI and SL). The equations were predicted using sixty undisturbed fine-grained soil samples collected from twelve different locations at Sulaimani City in Kurdistan Region of Iraq. Statistical analysis has been carried out by using SPSS software (Version 24). Coefficient of determination (R 2 ) and root minimum square error were used as an evaluation criterion in order to check the calculated empirical correlations equations. The statistical analysis showed that there is a direct and positive correlation among the selected parameters. In addition, accurate correlations were obtained in comparison to the existing relationships.
Keywords: Correlation; Compressibility; Consistency; Fine-grained Soils